Tafsir Kontemporer sebagai Metode Pembaharuan Pemikiran Politik Islam - Muflih Fahmi Kaunain; Faqih Al-Aziz (Resolusi: Jurnal Sosial Politik, 2018)
Poverty, legal injustice, discrimination, non-fulfillment of human rights and so on are the world's problems arising from development and modernity. But modernity as a result of the innovative nature of human beings is inherent in the world community and can not be abandoned. If we drag it even further, this shift depends on how the policies of the state overcome it. The existing political problems are the point of accumulation of the details of human affairs. Thus, where is the role of Al-Quran in this dynamic world? Islam as the world's largest religion with a very significant growth must be able to contribute to the problems of the world at hand, and should not be the problem trigger. Al-Quran is intended as an Islamic religion, capable of being used for all aspects of human life (sholihun fi kulli zaman wal makan). In fact, Islam today is believed as a world problem correlated to terrorism, civil war and the rise of Muslim refugees. In light of these things, intensiving the interpretation of contemporary political verses in accordance with the present age is a must. Interpretation methods must also be critical so that Islam can be used in various parts of the world. This paper will examine how to seek contemporary interpretation with various divisions and by combining classical interpretation methods that are expected to emerge strong interpretations. Contextualization of the political verses became the focus of the method which was then connected with the spirit of the verse to be applied in the present. In addition, the interpretation is also supported by the analysis of language, analysis of the verses and hadiths that has similar topics, and contextualization with the current conditions. With this new method of interpretation, it is expected that the Qur'an can be a solution for Muslims and the world community in general. Furthermore, Islam is able to initiate the civilization of a just world.